The Effectiveness of Trichoderma Harzianum and Trichoderma Viride to Inhibit Pathogenesis Of Rhizoctonia Solani agianst Tomato Plant - Intesar, Mezeal Ali; Liqaa, Ibraheem Jameel; Shaimaa, Mizil Nghamish (Arab Journal for Sciences and Research Publishing, 2016)
In vitro testing, antagonistic capability of Trichoderma spp. obtained from the rhizosphere of tomato showed inhibitory effect against growth of R. solani , few biological control agents have achieved success under field conditions. Among the hundreds of organisms identified as potential biological disease control agent, only few have resulted in proving commercially acceptable control of these diseases. Rhizoctonia solani were isolate from a naturally occurring epidemic of damping-off tomato plants grown in Kut governorate, Iraq,In vitro, of 9 isolates belonging to the fungus Trichoderma spp. 5 isolates belonging to the fungus T. viride while diagnosed 4 isolates belong to the fungus T. harzianum isolated from the rhizosphere of tomato plants. Both T. viride and T. harzianum had antagonistic effect on R.solani isolates . Results showed that ability of six isolates of the pathogenic fungus to damping of the tomato plant seedlings under greenhouse conditions , isolates R.solani-M and R.solani-H showed the largest percentage of the disease compared with other isolates( 30.2 and 32.1%) respectively, while the effect of isolate R.solani-A was daming of 21.9% from tomato seedlings Pre-emergence.